2012
DOI: 10.1016/j.rmed.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Inhaler mishandling is very common in patients with chronic airflow obstruction and long-term home nebuliser use

Abstract: Inhalers and nebulisers are devices used for delivering aerosolised drugs in subjects with Chronic Airflow Obstruction (CAO). This multicentre, cross-sectional observational study was performed in a large population of outpatients with CAO regularly using home aerosol therapy and referring to chest clinics. The aims of the study were to compare the characteristics of the group of subjects with CAO who were using home nebulisers but also experienced with inhalers vs. those only using inhalers and to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 24 publications
0
32
0
2
Order By: Relevance
“…Between 36 and 49% of patients with COPD perform critical inhaler errors with currently used inhalers, 18,19 and in a review of studies by Cochrane et al 20 efficient inhalation technique was demonstrated by only 46–59% of asthma patients. The development of an easy-to-use inhaler device that delivers the drug to the lungs effectively is important.…”
Section: Introductionmentioning
confidence: 99%
“…Between 36 and 49% of patients with COPD perform critical inhaler errors with currently used inhalers, 18,19 and in a review of studies by Cochrane et al 20 efficient inhalation technique was demonstrated by only 46–59% of asthma patients. The development of an easy-to-use inhaler device that delivers the drug to the lungs effectively is important.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-reported measures include the Short Form Chronic Respiratory Disease Questionnaire [19], a chronic disease self-efficacy scale [20] adapted to COPD, COPD Assessment Test [21, 22], the short version of the Patient Assessment of Chronic Illness Care (PACIC) [23], the Patient Health Questionnaire (PHQ-8) [24], the Generalized Anxiety Disorder Scale [25], the Morisky Medication Adherence Scale [26, 27], the Trust in Physician Scale [28, 29], a single-item health literacy screener [30], and a modified version of an inhaler use checklist [31]. The timeline of these measures is shown in Table 1 below.…”
Section: Methodsmentioning
confidence: 99%
“…However, while Hawthorne effects have been described , these effects seem to be reducible if the observation spans across a longer period of time . Direct observation can also be employed with patients or family members to detect administration errors when using inhalers , insulin pens , eye drops , parenteral drugs or per oral drugs , for instance. Such assessments form the basis to describe the epidemiology of administration errors as well as other influencing variables and are essential to describe the benefit of potential error prevention strategies.…”
Section: Resultsmentioning
confidence: 99%